Perlindungan Hukum Terhadap Keamanan Rahasia Bank dalam Menjaga Kepentingan Nasabah Perbankan - Ahmad, Hakam; Anggraini, Sri; Iswahyudi, Gesang (Fakultas Syariah INSURI Ponorogo, 2022)
Banking is a driving force for national development. In order to avoid misappropriation of customer finances, it is necessary to make rules that prohibit banks from providing registered information to anyone relating to customer finances and deposits as regulated in Law Number 10 of 1998 concerning Banking except in certain cases which are explicitly stated in the Act. the law. The security of bank secrecy needs to be safeguarded under the legal umbrella for the benefit of customers and bank security. Violation of this provision is considered a banking crime and can be subject to criminal or civil sanctions. The conclusion in this thesis is that bank secrecy is important because banks as financial institutions are obliged to provide protection to customers. The research in this thesis uses the normative legal method which is carried out or aimed only at written regulations and or legislation, legal principles and expert opinions. This type of research is qualitative through a literature review (Library Research).